Incidental Rickets in the Emergency Department Setting - John V. Zurlo; Shaun R. Wagner (Case Reports in Medicine)
Vitamin D deficiency rickets is a childhood osteomalacia, with impaired skeletal development and potentially skeletal deformities. The radiographic findings of rickets are many but include widening, fraying, and cupping of the metaphysis. Developmental delay and related complications of seizure and tetany have also been reported. This medical entity is often thought of as a classic medical disease of the past. However, it persists, and the recognition of rickets is on the rise. The reemergence of rickets correlates with the increase in the number of children exclusively breastfed and with the frequent use of sun block in the pediatric population. We present two cases of rickets, diagnosed through a visit to the Emergency Department made for unrelated symptoms. These two cases illustrate the importance of diagnosing rickets as an “incidental” finding. With early detection, dietary supplementation can be initiated potentially sparing the patient symptomatic disease.